African immigrants’ favorable preterm birth rates challenge genetic etiology of the Black-White disparity in preterm birth - Braveman, Paula; Heck, Katherine; Dominguez, Tyan Parker; Marchi, Kristen; Burke, Wylie; Holm, Nicole (Frontiers in Public Health, 2024)
Background We examined over a million California birth records for 2010 through 2021 to investigate whether disparities in preterm birth (PTB) by nativity and race support the widely held but hitherto unsubstantiated belief that genetic differences explain the persistent Black-White disparity in PTB. Methods We examined PTB rates and risk ratios among African-, Caribbean-, and U.S.-born Black women compared to U.S.-born White women. Multivariate analyses adjusted for maternal age, education, number of live births, delivery payer, trimester of prenatal care initiation, pre-pregnancy BMI, smoking, and prevalence of poverty in a woman’s residence census tract; and for paternal education. Results In adjusted analyses, African-born Black women’s PTB rates were no different from those of U.S.-born White women. Discussion The results add to prior evidence making a genetic etiology for the racial disparity in PTB unlikely. If genetic differences tied to “race” explained the Black-White disparity in PTB among U.S.-born women, the African immigrants in this study would have had higher rates of PTB, not the lower rates observed. Multiple explanations for the observed patterns and their implications are discussed. Failure to distinguish causes of PTB from causes of the racial disparity in PTB have likely contributed to erroneous attribution of the racial disparity to genetic differences. Based on the literature, unmeasured experiences of racism, including racism-related stress and adverse environmental exposures, are plausible explanations for the PTB disparity between Black and White U.S.-born women. The favorable birth outcomes of African-born Black immigrants may reflect less exposure to racism during sensitive life periods, e.g., childhood, when they were in African countries, where Black people are in the racial majority.